2023
DOI: 10.1002/hyp.15003
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of runoff and hydrological drought changes in an ecologically vulnerable basin in semi‐arid regions of China

Xinyue Li,
Yuntao Wang,
Baolin Xue
et al.

Abstract: Climate change and human activities have been widely recognized as two major factors that deeply influence hydrological processes. Evaluating and identifying the contribution between different drivers contributes to better regional water management regulation. In this study, we used the variable infiltration capacity (VIC) model to quantify the contributions of different climatic variables and human activities to runoff in the Hunhe basin, which has a semiarid climate, in northern China. Through trend analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Air pollution affects ecosystem security, climate change, the COVID-19 pandemic, economic development and human health (Bashir et al, 2020;Ma et al, 2021;He et al, 2022;Xue et al, 2022;Alahmad et al, 2023;Guo et al, 2023b;Li et al, 2023). According to the World Health Organization (WHO) assessment report, 99% of the world's population lives in environments where air quality exceeds the recommended values of the WHO Air Quality Guidelines (AQG) (annual average PM2.5 concentration < 5 µg m -3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution affects ecosystem security, climate change, the COVID-19 pandemic, economic development and human health (Bashir et al, 2020;Ma et al, 2021;He et al, 2022;Xue et al, 2022;Alahmad et al, 2023;Guo et al, 2023b;Li et al, 2023). According to the World Health Organization (WHO) assessment report, 99% of the world's population lives in environments where air quality exceeds the recommended values of the WHO Air Quality Guidelines (AQG) (annual average PM2.5 concentration < 5 µg m -3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main analytical methods include the hydrological modeling method [16], the multivariate statistical analysis method [17,18], and the empirical modeling method [19]. Hydrological models have certain physical mechanisms that are suitable for the hydrological simulation of watersheds of different scales and complexity [20][21][22]. The model requires high data accuracy and continuity, although there are large uncertainties in the model parameters and structure [23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that vegetation greening in humid areas has not substantially reduced runoff and soil moisture in watersheds by enhancing water recirculation, whereas this has not been the case in arid areas [17]. In arid regions, vegetation greening might lead to a series of negative ecohydrological effects in watersheds, such as reduced river runoff, insufficient ecological water demand, soil salinization, and reduced species diversity [18,19]. Wu et al [20] found that the main cause of runoff attenuation in the transition zone between the Qinling Mountains and the Loess Plateau was vegetation greening.…”
Section: Introductionmentioning
confidence: 99%